Laborn Reform: An Overview A study of their history, gestation, reception, legal characteristics, rationale, content and assessment (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This paper studies the origins and gestation of the reform and its contents, at the same time providing an overview and an evaluation of the same. Along with the socio-political aspects which accompanied the advent of reform, is a legal analysison the technique used, issues of constitutionality and scope of different forecasts of the law regarding its virtuality to alter the model of labour relations.
Keywords: Labor reform; Background; Gestation and reception of the reform; Legislative technique; Problems of constitutionality; Latest Foundation; News cast and its valuation.